PbF2–CdF2–SrF2 Ternary Solid Solution: Crystal Growth and Investigation - Irina I. Buchinskaya; Ivan O. Goryachuk; Nikolay I. Sorokin; Victor I. Sokolov; Denis N. Karimov (Condensed Matter, 2023)
Crystals based on alkaline earth metal difluorides are widely used optical materials. In this study, in order to expand the range of optical matrices, multicomponent Pb1−x−yCdxSryF2 (0.27 < x < 0.55, 0.06 < y < 0.18) solid solution crystals with a fluorite structure (sp. gr. Fm-3m) were grown from melt using the vertical directional crystallization technique for the first time. The densities and refractive indices of the grown crystals vary depending on the quantitative content components (x and y) in the ranges of 6.6039(5)–7.5232(5) g/cm3 and 1.6403–1.7084, respectively. The optical transmission and electrochemical impedance spectra were studied. The homogenous composition regions of non-cellular crystallization of this ternary solid solution at a crystallization rate of 6 mm/h and an interface temperature gradient of 80 deg/cm were experimentally determined as 0.30 < x < 0.35, 0 < y < 0.6. These grown crystalline materials may be of interest as high-density highly refractive cubic isomorphic hosts and low-temperature ionic conductors (~2 × 10−5 S/cm at room temperature) for various applications.